Methodology Of Addition And Subtraction Of Fractions - Abdurakhimova, Mardona (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This paper discusses the methodology of teaching addition and subtraction of fractions in primary school mathematics. The main goal is to develop students’ understanding of fractional numbers and to form strong skills in performing arithmetic operations with fractions consciously and correctly.The study explains the methods of adding and subtracting fractions with the same and different denominators, as well as operations involving mixed numbers. Special attention is given to the effectiveness of using visual aids, interactive teaching methods, and modern information technologies to enhance lesson quality and student engagement.The results show that using visualization, step-by-step teaching, and interactive approaches in teaching fractions improves students’ independent thinking, analytical abilities, and practical application skills in mathematics